AGILE IMPLEMENTATION IN MOBILE POINT OF SALE SYSTEM DEVELOPMENT FOR BUSINESS DIGITALIZATION - Yudha Herlambang Cahya Pratama; Farhan Abimanyu Firmansyah; Laqma Dica Fitrani (Jurnal Riset Informatika, 2026)
The development of information technology drives the need for a flexible, efficient, and easy-to-use Point of Sale (POS) system to support retail business operations. This study aims to design and develop a mobile-based POS application using Agile methods to improve the effectiveness of transaction management and sales data. The research methods include problem identification, needs analysis, system design, application development, testing, and iterative system evaluation. The system design was carried out using use case diagrams and Entity Relationship Diagrams (ERD), while the implementation was developed on a mobile platform with key features including user authentication, product management, sales transactions, stock management, reports, and owner and cashier access rights settings. Quantitative evaluation using Black-Box testing validated a 100% functional success rate across all core modules, ensuring operational stability. Test results show that the application is able to function optimally, responsively, and stably in supporting real-time business processes. The simple and intuitive user interface facilitates system operation, while the Agile approach allows for continuous feature adjustments. Performance metrics also indicated a 40% reduction in average transaction processing time. Thus, the developed application is considered effective in improving the efficiency, accuracy, and quality of mobile-based retail transaction management